Directions of application of international experience of staffing of forensic institutions in ukraine - Hasparian, Serafyma (Archives of Criminology and Forensic Sciences, 2020)
The article stipulates that national forensic examination can not exist in isolation, only within a single state, it is essential for forensic institutions to promote international cooperation in order to exchange experience, take into consideration modern achievements of science and technology, create specialized areas for expert research. It is stressed that forensic institutions of Ukraine have chosen the path of joining the communities of international forensic institutions, making it possible to improve staffing. The author noted that the purpose of the community of European forensic institutions is to promote: science and research in the field of forensic science; international cooperation in the field of forensic activities; quality of expert research and competence of forensic experts; education and training of forensic experts; developments in forensic science. It is emphasized that the realization of integration of forensic activities, as a result, always aims at harmonizing and improving expert legislation, deepening the theoretical foundations of forensic science, developing of common guidelines for different types of examinations, obtaining international recognition of expert opinion in general, further developing of forensic science, improving professional skills of the staff of forensic institutions. It is proved that as a result of the analysis of foreign experience of forensic institutions staffing the following directions of its possible implementation in Ukraine were suggested, such as: development of the European model of ensuring maximum independence and competition of forensic experts; intensification and expansion of participation in the international network of forensic institutions; focus on the training of forensic experts from the «children’s university» on the basis of higher education institutions, which also provide for appropriate internship programs; practice of experts training according to corresponding program under the guidance of a mentor from among highly qualified forensic experts; application of the combined extraordinary certification of forensic experts in case of reasonable doubts as to the required level of professional training, etc.